(untitled) (Ágora Journal, 2025)
This article investigates the interaction between politicians and lawyers in the distribution of social subsidies to philanthropic institutions in Brazil, focusing on the period following the administrative reforms of the 1930s. The study highlights how reforms aimed at modernizing and centralizing state control inadvertently facilitated the emergence of clientelistic practices within established bureaucracies. Based on the analysis of administrative processes and documentation from the Ministry of Justice and Home Affairs, the research identifies how politicians and lawyers used their positions and expertise to manipulate access to public resources, thereby subverting the objectives of social policies in favor of private interests. The article provides a critical reflection on the persistence of clientelism in Brazilian public administration despite continuous efforts toward institutional reform.